English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

h (x) = 4x + 3 function table

the table looks like this:
x......... h(x)=

-5 =
-1 =
0 =
3 =
5 =


I am still new at starting these

2006-11-05 09:42:42 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

sorry,
I got this:

-2,6,7,10,12

2006-11-05 09:44:18 · update #1

Please correct my work

2006-11-05 09:44:44 · update #2

I have been-
I keep getting
the remaining as folows:
-1=0
0=3
3 = 25
5=23

2006-11-05 09:52:55 · update #3

4 answers

h(-5)= -17
h(-1) = -1
h(0)= 3
h(3)=15
h(5) = 23

2006-11-05 10:00:21 · answer #1 · answered by MollyMAM 6 · 0 0

Just substitute each value of x into your equation and solve to find h(x).

For example, when x = -5, then h(x) = 4(-5)+3 = -20+3 = -17.

So put -17 under h(x) on the same line where -5 is.

Continue in this manner for the remaining values of x (-1, 0, 3, and 5).

Does that help you understand it better?

EDITED TO ADD: Just saw your answers that you posted. They are all incorrect. Now that I've explained the problem, try again and see what answers you get.

Here I will do another one for you to help out:

x=-1, so h(-1) = 4(-1)+3 = -4+3 = -1

2006-11-05 09:44:04 · answer #2 · answered by Anonymous · 0 0

All you have to do is substitute the data is given in the table in for (x)

it look like these here:

for -5
h(-5)= 4(-5) + 3
= -20 + 3
= -17

for 0
h(0)= 4(0) + 3
= 0 +3
= 3

2006-11-05 09:49:23 · answer #3 · answered by Anonymous · 0 0

oh my god i hate that! hmmm...had that as quickly as i replaced into on my 0.33 twelve months! analytic! grrrrrr....oh properly attempt to stay with the formulation and replace. confirm you word the equation cuz one errors would be particularly some soreness interior the in the back of.

2016-10-21 07:56:09 · answer #4 · answered by ? 4 · 0 0

fedest.com, questions and answers